ANALISIS TEKANAN DARAH LANSIA YANG MELAKUKAN KEGIATAN OLAHRAGA JALAN PAGI - Gamya Tri Utami; Wasisto Utomo; Mustika Riolita (Fakultas Keperawatan, Universitas Riau, 2016)
The purpose of this study was to analyze differences in blood pressure of elderly who do morning sportsactivities in PSTW Khusnul Khatimah Pekanbaru. The research design was quasy experimental design withnon-equivalent control group. The samples were 30 people which divided into experimental group and controlgroup. Sampling method used nonprobability sampling with inclusion criteria. Data were analyzed usingunivariate and bivariate data analysis. Univariate analysis used to see the form of numerical variables,namely blood pressure by looking at the mean, median, standard deviation (SD), minimum and maximumvalues. The bivariate analysis using repeated ANOVA test and independent T test. The results showed thatsystolic blood pressure measurement indicate a difference in the average blood pressure in those who exercisebrisk walking for 3 weeks (3x, 6x, and 9x) with a p value of 0.008. As for the comparison between the elderlywho exercise a morning walk with the group that did not exercise the way morning showed a significantdifference to blood pressure systole with p value 0,010. This study suggests that exercise brisk walking ofthe elderly use as non-pharmacological alternative therapy to prevent the increase in blood pressure andmaintaining blood pressure remains stable.